2021
DOI: 10.3390/en14164823
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Comparison of DC and AC Coupling Solutions for Large-Scale PV+BESS Power Plants

Abstract: In large-scale photovoltaic (PV) power plants, the integration of a battery energy storage system (BESS) permits a more flexible operation, allowing the plant to support grid stability. In hybrid PV+BESS plants, the storage system can be integrated by using different power conversion system (PCS) layouts and different charge–discharge strategies. In the AC-coupling layout, the BESS is connected to the ac-side of the system through an additional inverter. In the DC-coupling layout, the BESS is connected to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…When the load of the system is disturbed so that the frequency change exceeds the regulation dead band, the photovoltaic power station should be able to respond to the change and make corresponding adjustments to restore the system frequency [11]. When the frequency meter changes due to load disturbance, the output of the photovoltaic power station shall be adjusted as follows:…”
Section: Photovoltaic Primary Frequency Modulation Action Modementioning
confidence: 99%
“…When the load of the system is disturbed so that the frequency change exceeds the regulation dead band, the photovoltaic power station should be able to respond to the change and make corresponding adjustments to restore the system frequency [11]. When the frequency meter changes due to load disturbance, the output of the photovoltaic power station shall be adjusted as follows:…”
Section: Photovoltaic Primary Frequency Modulation Action Modementioning
confidence: 99%
“…N recent years, DC distribution systems have grown in popularity due to their superiority over standard AC systems in terms of improving overall efficiency in buildings, particularly when renewable energy sources are integrated [1]. When the AC system is replaced with the DC system, studies have shown that a relative reduction in system loss of up to 2.3% [2] and an improvement in grid energy savings of 7% [3] may be obtained. The advantage of the DC system may vary based on geographical location, allowing renewable energy sources to contribute to matching the load demand of individual end-users throughout different seasons.…”
Section: Introductionmentioning
confidence: 99%
“…A similar concern is caused by the intermittent nature of RES, whose power generation strongly depends on the availability of the primary source (wind, solar, etc. ) and cannot usually provide the control and regulation services that conventional sources can do (Luo and Ooi, 2006;Kroposki et al, 2017;Lo Franco et al, 2021a). Intermittent power injection together with localized load power peaks (aggregate EV charging) might even bring to the nonoptimal utilization of conventional plannable power sources for grid supporting operation (ancillary services).…”
Section: Introductionmentioning
confidence: 99%